PRODUKTIFITAS KERJA PEGAWAI PEMERINTAH DAERAH (STUDI KASUS PADA PEMERINTAH DAERAH DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KABUPATEN ENDE) - , AGUSTINUS SAMBAR FRIDAY FRY, SS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Analysis of labor productivity become very important today because essentially covers the attitudes of staff should have a view that today should be better than yesterday. Assessment of labor productivity in the bureaucracy serves as an ingredient to sees how an organization achieve organizational goals by utilizing the time and resource to the maximum and maximum yield outcomes as well, so as to achieve agency in carrying out programs and activity objectively difficult to do because of the level of measurable success of the implementation of programs of a government agency. Research was took place in the Department Education of Youth and Sport of Ende District. Purpose of the study of this study is to provide an overview of the state of the Department Education of Youth and Sport of Ende District and the factors that influence it. The study used qualitative research methods with descriptive approach data collected through observation, interviews and secondary data. While the location of research in the organization of the Department of Education of Youth and Sport of Ende District. Result of this research shows that the productivity of employees working in the Department of Education of Youth and Sport of Ende District still runs not stable it can bee seen from the program that has not been achieved and programs have increased by the Department of Education of Youth and Sport of Ende District and factors that influenced, namely the lack of motivation, work discipline and capabilities of the employees of organization of the Department of Education of Youth and Sport of Ende District. To optimized the productivity of employees working in the Organization of The Department of Education of Youth and Sport of Ende District necessary training to increase to increase employee knowledge and skills, recruit employees who have knowledge of the administration of the organization, increasing trained professionals in each section and change the way employees through seminars on service in public administration.